2020
DOI: 10.3390/ijerph17020645
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Industry–Environmental System Based on Resilience Perspective

Abstract: The contradiction between industrial development and ecological environment pressure has been becoming progressively severe. Under this circumstance, more attention has been paid to the balance between industrial economic development and environmental deterioration and resource consumption. Thus, this study takes the development of industry and ecological environment change as an interactive system consideration, and comprehensively evaluates the changes of the industrial-environment system on resilience persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…In the face of more and more urban domestic waste and construction waste, how to deal with and make good use of these wastes from the perspective of ecological and environmental protection has become an important issue to be considered for the green and healthy development of modern cities. From the perspective of ecology, gradually realizing the resource utilization, harmless treatment, and reduction development of urban construction waste and domestic waste is an e ective means to solve urban waste scienti cally and e ectively [2]. erefore, from the perspective of ecological and environmental protection, starting with the development status of modern urban waste recycling, this paper focuses on the operation model and development path of urban waste recycling industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of more and more urban domestic waste and construction waste, how to deal with and make good use of these wastes from the perspective of ecological and environmental protection has become an important issue to be considered for the green and healthy development of modern cities. From the perspective of ecology, gradually realizing the resource utilization, harmless treatment, and reduction development of urban construction waste and domestic waste is an e ective means to solve urban waste scienti cally and e ectively [2]. erefore, from the perspective of ecological and environmental protection, starting with the development status of modern urban waste recycling, this paper focuses on the operation model and development path of urban waste recycling industry.…”
Section: Introductionmentioning
confidence: 99%
“…Para abordar el tema de prevenir o contrarrestar el deterioro ambiental y la sustentabilidad, se parte, por añadidura, del carácter multisectorial y sistémico de los temas ambientales; así como por la no-linealidad de determinados fenómenos productivos, ambientales y sociales. Así, se ha pasado por un largo proceso de identificación de problemas del detrimento ambiental antropogénico; pero finalmente se aceptó que, a mediano y largo plazos, se presentarían situaciones de deterioro que harían peligrar los equilibrios ecológicos y la salud humana, no solo en países industrializados (Wan et al 2020), sino además en países en vías de desarrollo semiindustrializados (Nadal 2007).…”
Section: Revisión De Literaturaunclassified
“…13 Wan et al have used the concept of environmental performance index (EPI) and industrial structure entropy (ISE), which were applied to analyze the current environment pressure and industrial conditions. 14 Liu et al reported on a unit basis, a ton of aluminum production requires ∼126 GJ of energy. 15 In another study of Liu et al, 16 for the Henan province of China, 18 aluminum smelters were examined for energy efficiency in the alumina production process.…”
mentioning
confidence: 99%